Pengaruh Inovasi Produk Terhadap Minat Beli Konsumen di Era New Normal - Windah Pebriani; Nur Busyra (Jurnal EMT KITA, 2023)
This study aims to determine the effect of product innovation on consumer buying interest, especially in the New Normal Era. The research object chosen is Roti Unyil Venus Bogor which is considered representative because it is identified that they often innovate on their products. The research population comes from consumers who make transactions from February to April 2022, then the sampling technique is Cochran. The research method uses associative quantitative, the analysis technique uses simple linear regression with the stages of validity and reliability testing, classical assumption test, and simple linear regression test. The results show that product innovation has a positive and significant effect on consumer buying interest, with an R-Square value of 27.3%